Effectiveness of strategies to screen for blood donors with RH variants in a mixed population. (April 2020) - de Almeida, Fabio Augusto Abreu; Dezan, Marcia Regina; Oliveira, Valeria Brito; Alencar, Cecilia Salete; Luz, Fabio; Krieger, José Eduardo; Pereira, Alexandre Costa; Sabino, Ester Cerdeira; Rocha, Vanderson; Mendrone-Júnior, Alfredo; Dinardo, Carla Luana
Abstract: Introduction: Patients with RH variants presenting antibodies directed to RH high frequency antigens or multiple RH antibodies might, in some occasions, be better served with RH genotype-matched units, requiring screening for RH variants among blood donors. To date, strategies to identify donors with RH variants were restricted to selecting individuals of African descent based on self-reported race, what can be inaccurate in racially mixed population. Our goal was to: 1) Screen for donors with RH variants in a mixed population using self-declared race and Rh phenotype as selection criteria; and 2) Verify if including the Duffy null genotype in the screening algorithm increases its effectiveness. Methods: Brazilian donors were included if self-declared as black and phenotyped as R0r or R1r. All individuals were genotyped for RHCE exons 1, 5, 6 and 7 and for the FY*B c.−67 T > C polymorphism in order to determine the Duffy null genotype. RHD variants were searched for in cases of altered RHCE . Results: Among 2500 blood donors, 217 fulfilled the inclusion criteria and were enrolled. Fifty-three (24.4 %) had a predicted clinically relevant Rh phenotype (partial antigens or lack of high frequency antigens). Twelve donors (5.5 %) had a predicted RhCE phenotype lacking either hrB or hrS. Most cases with predicted lack of high frequency antigens (66.7 %) occurred in donors with the Duffy null genotype. Conclusion: Selecting donors based on self-declared race, Rh phenotype and Duffy null genotype is feasible and effective in identifying RH variants lacking Rh high frequency antigens among racially mixed donors.